Evaluating the effectiveness and implementation of evidence-based early-life nutrition interventions in a community setting a hybrid type 1 non-randomized trial – the Nutrition Now project protocol - Øverby, Nina Cecilie; Hillesund, Elisabet Rudjord; Helland, Sissel Heidi; Helle, Christine; Wills, Andrew Keith; Lamu, Admassu Nadew; Osorio, Natalie Garzon; Lian, Henrik; Ersfjord, Torunn Iveland; Van Daele, Wim; Bjørkkjær, Tormod; Valen, Erlend Nuland; et al. (Frontiers in Endocrinology, 2023)
Disappointingly few efficacious health interventions are successfully scaled up and implemented in real world settings. This represents an evidence-to-practice gap, with loss of opportunity to improve practice. Aiming to improve nutrition in the first 1000 days of life, we have combined four efficacious dietary interventions into a single adapted digital resource (Nutrition Now) for implementation in a Norwegian community setting. Nutrition Now targets pregnant women and parents of 0–2-year-olds with messages focusing on healthy dietary behaviours. Early childhood education and care (ECEC) staff are provided with pedagogical tools addressing healthy food exposure and child food acceptance. Objectives: a) evaluate the effectiveness of provision of the Nutrition Now resource on child diet and diet-related outcomes, with special attention to the influence of socio-economic position, b) gather information on the effectiveness of the implementation process to inform forthcoming scale-up and c) perform trial- and model-based economic evaluations. This is a hybrid type 1 implementation study, focusing on evaluation of effectiveness. A quasi-experimental design with pre- and post-tests, where one municipality gets access to the resource (n~800), while a matched non-equivalent control municipality (n~800) does not, will be used. Effectiveness will be assessed by examining e.g., diet outcomes, developmental outcomes, and feeding practices. The resource will be implemented in ECEC settings and made available to pregnant women and parents through the Norwegian system of maternal and child health (MCH) care. The implementation process includes iterative adjustments and implementation strategies from the implementation framework Expert Recommendations for Implementing Change (ERIC) informed by dialogues with stakeholders. Implementation outcomes (e.g., acceptability and adoption) will be assessed through questionnaires and interviews with parents, ECEC and MCH staff, with particular attention to ethnic diverse groups. Both within-trial and modelling-based economic evaluation will be performed. Nutrition Now will bridge the existing evidence-to-practice gap through rigorous scientific effectiveness evaluation of municipal scale up and inform subsequent county scale up. The study is the first to implement efficacious nutrition interventions in early life with potential for health improvement using technology to maximise the reach and impact of both parental and MCH dietary guidance and ECEC practice.